Biodegradation of polyvinyl chloride by Mucor s.p. and Penicillium s.p. isolated from soil - Pardo-Rodríguez, María Luisa; Zorro-Mateus, Patricia Joyce Pamela (Universidad Pedagógica y Tecnológica de Colombia, 2021)
PVC is one of the most widely used plastics today and the one that produces the most waste. In recent years, microorganisms capable of degrading it have been reported, most of which come from environments in which PVC is accumulated. The aim of this work was to study the degradation of PVC without plasticizer, from fungi isolated from a soil sample contaminated with PVC resin. The fungi were isolated and morphologically characterized, 30 morphospecies were obtained, 8 were chosen to undergo preliminary tests in a medium whose only carbon source was a PVC film. Growth curves of the two isolates with better results were made and their molecular identification showed that they corresponded to Penicillium sp. and Mucor sp., the latter gained biomass from PVC and in both cases, the films showed visible changes, which were supported by infrared spectra. Although the results shown in this article are preliminary, they open the door to new forms of PVC waste degradation that are very persistent.